Managing peformance as a system in human resources management and an application in banking sector - Ayvaz, Ece (My University, 2006)
Bu çalışmada performans ve sistematik performans yönetimi, ölçümü ve değerlendirmesi konusunda literatür araştırması yapılmış olup bankacılık sektöründe bir uygulama ile karşılaştırılmıştır. Uygulama örneği Türkiye’de faaliyet gösteren büyük bankalardan bir tanesidir. Çalışmada uygulamanın ayrıntıları sistematik olarak anlatılarak literatürle arasındaki benzerlikler ve farklılıklar ortaya konmuştur. Sonuç olarak her organizasyon kendi organizasyonel yapısı, personel sayısı ve sektörel özelliklere göre performans yönetim sistemi kurmakta, geliştirmekte ve uygulamaktadır. Abstact In this paper, managing performance systematically and measuring performance has been studied and a comparison made with an application in banking sector. For the study of application example, one of the most known banks in Turkey has been chosen. In the study detailed similarities and differences of literature and application has been identified and told clearly and systematically Finally it has been concluded that the application, development and settings of performance management systems in organizations depend on many factors like organizational structure, personnel and sectoral qualifications.
Keywords: Personel Yönetimi; Personel Yönetimi_Bankacılık